MENINGKATKAN PRESTASI BELAJAR IPA DENGAN MENERAPKAN METODE STUDENT TEAMS ACHIEVEMENT DIVISIONS BERBANTUAN CD PEMBELAJARAN PADA SISWA KELAS IV SEMESTER 1 DI SD N KARANGTOWO - suratmi, Suratmi (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2016)
Learning science in elementary school are learning that should be understood students tounderstand the various problems that occurred in the neighborhood. The subjects were fourthgrade students of Karangtowo elementary school Karangtengah District of Demak district by thenumber of students 27 students. Issues to be discussed include how to improve learningachievement and behavioral changes after making science learning material structure andfunction of plant parts in the fourth grade students of Karangtowo elementary schoolKarangtengah District of Demak district after learning method STAD with the applicationlearning CD. This study uses classroom action research design with two cycles. Each cycleconsists of action planning, action, observation, and reflection. Before taking action done priorlearning pre-cycle ago, which is used as the basis for corrective actions implemented.Results of preliminary tests prior to the act of research, namely in pre-cycle average valueobtained at 66.30. Because the value obtained student in materials science learning structure andfunction of plant parts are still considered very poor, so it needs to be implemented correctiveaction learning cycle I. In the first cycle the average value obtained for class 78.89. Values areachieved by students in the first cycle have been increased quite dramatically, but the valueachieved is still quite a lot that has not reached the minimum standards in the standar value is73.00. In addition, the participation of students is not yet active. There are still a lot of quite a lotof students are shy in presenting their opinions and ask questions. However, participation ofstudents in the first cycle is much better than before the implementation of the action. Based on theresults achieved, it is necessary to repair the holding of the second cycle. In the second cycle ofthe value achieved by students has increased very significantly by an increase of 86.30.Participant enthusiasm of the students and of students in the second cycle is much better. Therehave been many students who dared to ask and answer various matters relating to the learningscience material structure and function of the plant.